PKM Edukasi Keperdataan Kasus Bullying Terhadap Anak Pada Sekolah MTsN 1 Makassar - Amirullah Amirullah; Nurharsya Khaer Hanafi; Dalilul Falihin; Muhammad Rasyid Ridha (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
The results of research on the civil aspect of cases of bullying against children at educational institutions can be concluded that the practice of bullying still often occurs in educational institutions, for example at Mangkura V Elementary School, where students at the elementary school still carry out bullying behavior, although based on the results of bullying interviews. what is done is still at the level of verbal and non-verbal bullying. Therefore, the settlement efforts are carried out using a persuasive way, even though it has not injured the victim, it is better if there is still bullying, civil efforts can be taken both through lawsuits and non-litigation channels, especially if what happened was physically harming the victim, then a request for damages incurred experienced by the victim can be done, considering this phenomenon occurs in an environment that involves minors.